PARTISIPASI MASYARAKAT DALAM PENDIDIKAN - Anisa Dian Andini; Romlah Harniati Hapsah (CV. ADIBA AISHA AMIRA, 2025)
Education is the origin of a student of knowledge. Therefore, a student of knowledge is asked to deepen the various aspects he has learned. Seeking knowledge is not only about studying books in the library or textbooks, but understanding all fields that he feels he is capable of in several contexts, then he applies them in everyday life, then he is useful for those around him. Therefore, parents have a very important role for their children in the future. Parents are one of the first and foremost people in guiding their children. Achievement is not a benchmark in education, but experiences and opportunities that not everyone can feel. Parents are asked to be able to carry out the task of carrying out the mandate from the Almighty. Because children are the most beautiful gift.